THE INFLUENCE OF TOURISM VARIABLES ON REGIONAL ORIGINAL INCOME IN DISTRICTS/CITIES OF EAST NUSA TENGGARA PROVINCE (NTT) - Yohana Feradila Indah Teren; I Gusti Wayan Murjana Yasa (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
East Nusa Tenggara Province is a fairly well-known tourist destination. Tourism is an important sector in regional economic development in East Nusa Tenggara (NTT) Province. NTT's various natural, cultural and special interest tourism potentials are highlighted as attractions for tourists. However, even though this potential is large, there are disparities in development between regions in NTT. Some regions have experienced a significant increase in regional economic contribution, while other regions still need to evaluate economic development strategies. With the increase in the number of hotel rooms and restaurants which are not only a place to stay but also as a driver of development and regional income generation. The aim of this research was to evaluate the influence of several tourism variables such as the number of tourist attractions, number of hotel rooms and number of restaurants on Regional Original Income (PAD) in NTT. This research design uses a quantitative approach in associative form. The data collection method is by non-behavioral observation and the number of observations is 176. The types of data used are qualitative data and quantitative data. The data source used in this research is secondary data. This research uses a panel data analysis method. The research results found that the number of tourist attractions, the number of hotel rooms and the number of restaurants simultaneously had a significant effect on Regional Original Income (PAD) in the Regencies/Cities of NTT Province. The number of tourist attractions partially has a positive and significant effect on Original Regional Income (PAD) in the Regencies/Cities of NTT Province. The number of hotel rooms partially has a positive and significant effect on Regional Original Income (PAD) in the Regencies/Cities of NTT Province. The number of restaurants partially has no effect on Regional Original Income (PAD) in Districts/Cities of NTT Province.